Histopathologic features of adnexal tumors - Sandoval Paredes, José (2017)
About 1 in 10 women will present an adnexal tumor in her life and most will require surgical evaluation to rule out a malignant nature considering that risk of malignancy increases with age. Objective: To determine the frequency and malignancy of adnexal tumors by age, location and malignancy. Design: Descriptive, cross-sectional study. Setting: Ginecology and Gynecologic Oncology Services, Hospital Nacional Arzobispo Loayza, Lima, Peru. Material: Histopathology registries. Methods: Review of histopathology results of 876 patients who had surgery in 2013-2014 for adnexal tumor, that included anexectomies, oophorectomies, hysterectomies with adnexectomy and both paratubarian and paraovaric tumors. Main outcome measures: Tumor frequencies, localization and malignancy. Results: Out of 876 adnexal tumors, 73% were ovarian pathology, 14% tubal and 13% paratubal; 7% (61) were malignant. From the 482 benign ovarian tumors, serous cystadenoma corresponded to 282 (67.5%) cases. Mature teratomas occurred in average 32-year-old women. Out of the 61 cases of malignant ovarian tumors, which presented to women with an average age of 63 years, 26.2% were papillary serous adenocacinoma. Conclusions: Serous cystadenomas were the most frequent adnexal tumors. A high percentage of non-neoplastic ovarian tumors were found (18.8%); 7% of the tumors were malignant, and the most frequent of these was the papillary serous adenocarcinoma, which was diagnosed at an average age of 56 years.